Papillary thyroid microcarcinoma and papillary thyroid carcinoma: Clinical characteristics and stratification of treatment strategies - Congcong Li; Qiang Li; Xiao Shi; Shuang Han; Xiao Song; Xueqian Li; Xuewei Zhuang (PLoS ONE, 2025)
Aim Exploring the clinical differences between papillary thyroid micarcinoma (PTMC) and papillary thyroid carcinoma (PTC), optimizing clinical decision-making pathways, and reducing excessive medical behavior while ensuring therapeutic efficacy. Method Patients diagnosed with PTMC or PTC by pathological histology from May 2023 to May 2024 at Jinan Shizhong District People’s Hospital were retrospectively analyzed. PTMC refers to thyroid papillary carcinoma with a maximum diameter of ≤1 cm. Results There were 186 patients (PTMC group) whose maximum tumor diameter was ≤ 1 cm and 45 patients (PTC group) whose maximum tumor diameter was > 1 cm. The patient’s age was (45.97 ± 10.63) years for the PTMC group and (45.31 ± 11.55) years for the PTC group. No statistically significant differences existed between the two groups in sex, age, BRAF V600E gene mutation, tumor multifocality, and capsular invasion (P > 0.05). Between the two groups, there were statistically significant (P < 0.05) differences in TNM staging, the thyroid imaging reporting and data system (TI-RADS) staging, and cervical lymph node metastasis. Conclusions Thyroid surgery, thermal ablation, and active monitoring are different approaches in the stratified treatment of PTMC and PTC. To avoid overtreatment and improve the quality of life of the patients, personalized treatment plans should be developed according to the test results of TNM stage, TI-RADS classification, and cervical lymph node metastasis.